Assessment of the subchronic toxicity of ethanol extract of Merdeka-leaves (Chromolaena odorata L.) on SGOT, SGPT, and histological alterations in the kidneys and liver of male rats - Pertiwi, Reza; Azhar, Afra Wafiqah; Dominica, Dwi; Yudha, Salprima; Rahmawati, Reza; Putri, Yona Harianti (Pharmaciana, 2025)
The Merdeka plant (Chromolaena odorata L.) is known for its various pharmacological benefits, including gastroprotection, antibacterial, antihyperglycemic effects, and wound healing promotion. To ensure safe use in the community, it is important to evaluate its potential toxicity. This study examined the effects of ethanol extract of Merdeka leaf (C. odorata) on liver function by measuring the levels of serum glutamic-oxaloacetic transaminase (SGOT) and serum glutamic-pyruvate transaminase (SGPT) in male rats (Rattus norvegicus). Twenty-five male Wistar rats were split into five groups: three treatment groups that received ethanol extract at doses of 150 mg/kg BW, 300 mg/kg BW, and 600 mg/kg BW, a negative control group that received 0.5% Na CMC, and a normal control group that received no treatment. For 28 days, the extract was taken orally every day. Following surgery, liver and kidney tissues were removed for histology on day 29, and blood samples were obtained via the aorta. The findings demonstrated that rats administered 600 mg/kg BW of ethanol extract had significantly greater SGOT and SGPT levels than controls (p < 0.05), suggesting that high dose of Merdeka leaf extract may have an impact on kidney and liver functions.